HOW SOME INTERNAL FACTORS INFLUENCE CONSUMER BEHAVIOUR FOR PURCHASING CIGARETTES ON THE BULGARIAN MARKET: HOW SOME INTERNAL FACTORS INFLUENCE CONSUMER BEHAVIOUR FOR PURCHASING CIGARETTES ON THE BULGARIAN MARKET - Spasova, Veselina; Zhelev, Stefan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The purpose of the present research paper is to examine and analyze what internal factors influ-ence consumer buying behaviour for purchasing cigarettes on the Bulgarian Market. The study is limited to within the Bulgarian Tobacco Market. The factors were divided into two main categories: internal and external influences. The research focuses on the internal factors as age, gender, perception, motivation, lifestyle, atti-tudes.